SYSTEMATIC REVIEW PENGARUH PENDEKATAN SAINTIFIK TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS SISWA - Wicaksono, Anggit Grahito (Universitas Muhammadiyah Surakarta, 2020)
The purpose of the study was to investigate the effect of a scientific approach on improving students' critical thinking skills in various educational units. The research method used is a systematic review of research results available in the Indonesia One Search portal by analyzing qualitative research from each. From the results of the search for scientific publications, 33 scientific articles were obtained which were screened with inclusion and exclusion criteria obtained 5 articles. The results of this study revealed that (1) the scientific approach had a positive and significant influence on students' critical thinking skills in various educational units starting from elementary to high school. (2) the application of a scientific approach, especially in natural science learning (Physics, Biology, Chemistry) can improve students' critical thinking skills because the scientific approach has a strong and significant relationship with critical thinking skills. This systematic review research has implications in science learning based on a scientific approach in developing innovative learning models related to the empowerment of higher order thinking skills that include critical thinking, creative thinking, and problem solving.